2000
DOI: 10.1007/s002640000103
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity by dicloxacillin and gentamicin in 163 patients with intertrochanteric hip fractures

Abstract: Of 163 patients with intertrochanteric hip fractures 87 received 2 g dicloxacillin and 240 mg of gentamicin preoperatively, and 76 patients had no antibiotic prophylaxis. Preoperative antibiotic prophylaxis was not shown to have any significant effect on wound infections. However, 16 reversible and 1 irreversible cases of kidney toxicity were found among patients receiving antibiotic prophylaxis, whereas there were only four cases of reversible kidney damage among the patients not receiving antibiotics.Résumé … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Thirty‐six studies were included in the final synthesis: one thesis and 35 journal articles . The 36 studies included 11 randomized controlled studies (two crossover designs), 18 cohort studies, one retrospective survey, three pharmacokinetic and three quasiexperimental studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty‐six studies were included in the final synthesis: one thesis and 35 journal articles . The 36 studies included 11 randomized controlled studies (two crossover designs), 18 cohort studies, one retrospective survey, three pharmacokinetic and three quasiexperimental studies.…”
Section: Resultsmentioning
confidence: 99%
“…Reported adverse events are summarized in Table . Twenty‐three , of the 36 included studies, reported adverse events in the gentamicin arm of their study although not all adverse events were related to gentamicin. Pons et al .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, considering their substantial potential for toxicity even for fracture prophylaxis [92] and widespread use in the treatment of severe open fractures, there is a remarkable paucity of data concerning aminoglycoside use in this population [93]. Sangha et al [94] looked at the pharmacokinetics of oncedaily gentamicin dosing in a small series of intensive care patients with open fractures but did not comment on toxicity.…”
Section: Role Of Aminoglycosides and Fluoroquinolonesmentioning
confidence: 99%
“…Studies in orthopedic surgery were the most frequent (7 cohorts). The characteristics of the gentamicincontaining arm and the control arm were the most homogeneous in the orthopedic studies, with penicillin antibiotic (mostly flucloxacillin) and gentamicin in the exposure arm and cefuroxime in the control arm, except for one study (10) in which the control group used no antibiotic Failure to develop and apply appropriate eligibility criteria (inclusion of control population) Flawed measurement of both exposure and outcome Failure to adequately control confounding Incomplete or inadequately short follow-up Figure 5 Demonstrates the result of risk of bias assessment of each study.…”
Section: Discussionmentioning
confidence: 99%